2013
DOI: 10.3389/fimmu.2013.00310
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mucus Microstructure and Rheology in Helicobacter pylori Infection

Abstract: The bacterium Helicobacter pylori (H. pylori), has evolved to survive in the highly acidic environment of the stomach and colonize on the epithelial surface of the gastric mucosa. Its pathogenic effects are well known to cause gastritis, peptic ulcers, and gastric cancer. In order to infect the stomach and establish colonies on the mucus epithelial surface, the bacterium has to move across the gel-like gastric mucus lining of the stomach under acidic conditions. In this review we address the question of how th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
99
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 110 publications
5
99
0
1
Order By: Relevance
“…To reach its niche, this bacterium must escape the highly acidic gastric lumen and traverse the gastric mucus layer. Gastric mucins display pH-and concentration-dependent viscoelastic properties, behaving as a viscoelastic gel at low pH or high mucin concentrations (Ͼ25 mg/ml) and as a viscoelastic solution at neutral pH and lower mucin concentrations (61)(62)(63)(64). It has been proposed that H. pylori utilizes the corkscrew model to penetrate and traverse the mucus gel to escape the acidic lumen, which is consistent with the motility defects observed for straight and curved mutants in soft agar.…”
Section: Corkscrews and Wavessupporting
confidence: 57%
“…To reach its niche, this bacterium must escape the highly acidic gastric lumen and traverse the gastric mucus layer. Gastric mucins display pH-and concentration-dependent viscoelastic properties, behaving as a viscoelastic gel at low pH or high mucin concentrations (Ͼ25 mg/ml) and as a viscoelastic solution at neutral pH and lower mucin concentrations (61)(62)(63)(64). It has been proposed that H. pylori utilizes the corkscrew model to penetrate and traverse the mucus gel to escape the acidic lumen, which is consistent with the motility defects observed for straight and curved mutants in soft agar.…”
Section: Corkscrews and Wavessupporting
confidence: 57%
“…It is known that the formation of gels in gastric mucin at low pH develops also unique rheological features (Bansil et al, 2013;Celli et al, 2007;2005). Gels are characterized by a viscoelastic response originated by the combined effect of both solid-like and liquid-like behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Gelation of gastric mucus has been studied by several experimental techniques (Bansil et al, 2013;Hong et al, 2005). It has been concluded that conformational changes in mucin are developed as the pH is reduced to pH < 2.…”
Section: Introductionmentioning
confidence: 99%
“…Defects in mucin production can lead to diseases such as ulcerative colitis when mucins are underproduced or cystic fibrosis and asthma when mucins are overproduced (4)(5)(6). In addition, studies have shown that mucins can interact with microbes, such as Helicobacter pylori, Haemophilus parainfluenzae, and human immunodeficiency virus (7)(8)(9)(10). These diseases and microbial interactions highlight the necessity of mucins as one of the body's key natural defenses; however, few studies have focused specifically on the connection between MUC5B salivary mucins and oral diseases.…”
mentioning
confidence: 99%